Visual, Auditory, Kinesthetic Learning Styles In the perspective of the Qur'an - Juariah, Siti; Achmad, Yudianto; Edy, Sarwo (Proceeding International Pelita Bangsa, 2023)
Humans have different learning styles including: visual learning styles or based on vision; auditory learning style or based on hearing; and kinesthetic learning styles based on feelings. Learning styles in a scientific perspective already exist in the Qur'an, in Surah An-Nahl (16:78): learning style " السَّمْ ع "-"Al-Sam'a", which means learning based on hearing; learning style “ الْْ بْ صا ر ”-“Al-Abshôr”, which means learning based on vision; learning style " الْْ فْئِد ة "-"Al-Af'idah", which means learning based on feelings. This research conducted a study on learning styles in 100 students of SMAN 2 Cikarang Selatan. A learning style questionnaire was given to students and the results were analyzed. Based on the results of this study it can be concluded that 42% of students have a visual learning style, 32% have an auditory learning style and 27% have a kinesthetic learning style.